(untitled) (Journal of Parents and Teachers, 2020)
In this article we present an interview with Isabel Celaá (Bilbao, 1949), current Minister of Educación y Formación Profesional. The interview, arranged during the month of September on the occasion of the 55th anniversary of Padres y Maestros, it was celebrated on tuesday 10 november coinciding in time with the discussion of the LOMLOE. It was carried out by Professor Vicente Hernández, director of the journal during the last ten years. Beyond the initial objective of knowing the the minister’s views on the education of our country, we were able to echo the impact and controversies that are taking place in the processing of this new law.